Evaluation of 3s Center Layout on the Services Offered at Barangay Ugong, Valenzuela City: Residents’ Perspective: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Two key elements that are continually considered when planning and carrying out staffresponsibilities are layout and services. The interrelation between the two influences theattainment of a directed system toward its people. Researchers identified variables that mayhave an impact on the services provided inside 3s Center from Barangay Ugong, ValenzuelaCity. The purpose of this study was to assess the elements influencing the constituents'perception of the office layout at 3s Center in Barangay Ugong.Upon analyzing the data gathered in the study, the result shows a high level of satisfactionfrom the residents with regards to 3S Center Layout and its services. Locals are well guidedby the indicators used to describe their perspective about the layout as well as theirexperience with the services. Hereof, the total weighted mean of 3.65 was attained to showthe correlation between the two, and it proves that the layout certainly influences how theemployee performs and carries out services.In general, Layout and Services are two significant things to consider for a quality officeprocedure. It was evident from the evaluation conducted by one of the 3S Centers fromValenzuela City. It revealed a high level of satisfaction from the residents that led to a betterunderstanding and acceptance of innovative ways to use a system.
Keywords: Business Administration